Characteristics and Source-specific Health Risks of Ambient PM2.5-bound PAHs in an Urban City of Northern Taiwan - Yu-Chieh Ting; Chun-Hung Ku; Yu-Xuan Zou; Kai-Hsien Chi; Jhy-Charm Soo; Chin-Yu Hsu; Yu-Cheng Chen (Aerosol and Air Quality Research)
Abstract Polycyclic aromatic hydrocarbons (PAHs) with highly toxic compounds mainly exist in small-sized particles and can induce considerable human health risks. Studies on PM2.5-bound PAHs and their source-specific human health risks still remain scarce. Daily PM2.5 samples (n = 119) were collected every three days from 2016 to 2017 in Taipei city, Taiwan. Fifteen PAHs in PM2.5 were analyzed via gas chromatography tandem mass spectrometry (GC/MS-MS). We utilized a positive matrix factorization (PMF) model, diagnostic ratios, and potential source contribution function (PSCF) to identify the origins of PM2.5-bound PAHs. The annual concentration of total PAHs (TPAH) was 0.79 ± 0.67 ng m−3 (range = 0.11–3.27 ng m−3). The highest and lowest values of TPAH appeared in winter and autumn with a mean of 1.36 ng m−3 and 0.43 ng m−3, respectively. The contributions of high-molecular-weight PAHs (HMW PAHs) to TPAH were notably higher than those of low-molecular-weight PAHs (LMW PAHs) during the sampling period. Benzo[ghi]perylene (BghiP) accounted for the highest percentage (23.9%) of TPAH among selected congeners. Traffic emissions (31.3%) were identified as the predominant contributor to ambient PM2.5-bound PAHs, followed by industrial emissions (29.2%), evaporated/unburned oil (22.3%), and biomass/coal combustion (17.1%). Apart from the local sources, PSCF-derived results showed that emissions from industrial activities in northeast China and shipping around the Yellow Sea and East China Sea could affect the PAHs in the study area. Traffic emissions were the strongest contributor to human health risk, thus pointing to the significance of control over vehicle exhaust. This study suggests that it is necessary to distinguish the sources of the PM2.5-bound PAHs in order to underpin preventive and mitigative strategies for protecting environmental and public health.